Previsão de séries temporais: produção industrial e demanda de energia elétrica no Brasil - Pontes, Lucélia Pontes e (2018)
Forecasting is an important activity that can be developed in any space whose study is associated with the environment of predicting future behavior in relation to the events of interest. The objective of this work is to find through econometric modeling the best prediction model for the series of industrial production and residential electric energy demand in Brazil, using simpler individual models used as baseline (ARIMA), multivariate (ARDL) (VAR) and forecast combination. The best model was obtained through the statistics of the errors, through the performance of accuracy.